Dynamic hip kinematics during recreational classical ballet and hula dance after total hip arthroplasty: two case reports - Keisuke Komiyama; Satoshi Hamai; Daisuke Hara; Satoru Ikebe; Yifeng Wang; Hirotaka Gondo; Hidehiko Higaki; Yasuharu Nakashima (Journal of Medical Case Reports, 2019)
Abstract Background The in vivo assessment of the three-dimensional kinematics of the hip during dance activities in patients after total hip arthroplasty has not been previously reported. We evaluated the replaced hip kinematics during recreational classical ballet and hula dance using radiographic-based image-matching techniques. Case presentation A 58-year-old Japanese woman (patient 1; height, 157 cm; weight, 74.5 kg) and a 73-year-old Japanese woman (patient 2; height, 153 cm; weight, 48 kg) were still doing classical ballet and hula dance, respectively, after primary total hip arthroplasty. For ballet, there were gradual three-dimensional hip movements with 48° flexion, 36° abduction, and 49° external rotation in développé and 34° flexion, 29° abduction, and 43° external rotation in plié. For hula, there were small three-dimensional hip movements with 31° flexion, 15° adduction, and 11° external rotation in kao and 17° flexion, 11° adduction, and 11° external rotation in kaholo. No liner-to-neck contact was found in any dance activities. Conclusion Both classical ballet and hula dance produced complex ranges of hip movements and activity-dependent kinematics. These kinematic data could be useful for recommending each patient with total hip arthroplasty to continue recreational dance activities.